Documentos fotográficos da Secretaria Municipal de Finanças e Tecnologia da Informação - SEMEF - Chaves, Ingrid Gaspar (Brasil, 2024)
The present work consists of verifying the photographic collection of the Municipal Secretariat of Finance and Information Technologies (SEMEF) as an archive. SEMEF is a public administration body responsible for managing tax activities in the municipality of Manaus. In its activities, photographic records are produced. However, it was observed that there are no photographs present in the institution's permanent archive and that photographic records are not managed as archival documents. The work methodology will be exploratory in nature, observation of the institution and qualitative research. Interviews with SEMEF professionals will be used to collect information about the reality of the documentary treatment of photographs produced by the institution. In this sense, we intend to observe the way in which SEMEF understands its photographs as archival documents.